Exfoliated 2D black phosphorus nanosheets: field emission studies - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2016)
A few layer black phosphorus (BP) nanosheets are obtained by micromechanical cleavage from a bulk BP crystal. In a typical exfoliation procedure, a layer of BP is peeled off from bulk crystal with the help of Scotch tape and transferred onto SiO2/Si and pristine Si substrates. The morphological and structural analyses of the samples were carried out using an optical microscopy, a transmission electron microscopy, and a Raman spectroscopy. Field emission investigations on a few layered BP nanosheets on Si substrate were carried out at the base pressure of 1 x 10(-8) mbar. The turn-on value, corresponding to emission current density of similar to 1 mu A/cm(2), is found to be similar to 5.1V/mu m for BP nanosheets/Si emitter and high field enhancement factor (beta) similar to 1164, attributed to atomically thin/sharp edges of the BP nanosheets. The emission current shows good stability at a preset value of similar to 5 mu A over a period of more than 8 h. The present results demonstrate the potential of the mechanically exfoliated BP nanosheets/Si field emitter for the development of practical electron sources. (C) 2016 American Vacuum Society.